Peran Food Festival dalam Meningkatkan Citra Destinasi Kuliner Tradisional Surabaya - Mau, Daniel Pandu; Mau, Yesarela Pandu; Wibowo, Otje Herman; Kurniansah, Rizal; Artana, I Wayan Arta; Ariawan, I Wayan Adi Putra (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2024)
AbstractSurabaya, as a city with significant potential in the traditional culinary tourism sector, has not been fully optimized as a major culinary destination. This study aimed to explore the role of food festivals in enhancing Surabaya’s image as a traditional culinary destination. A qualitative research approach involved in-depth interviews with small and medium-sized enterprise (SME) actors, festival visitors, event organizers, observational analysis, and promotional material review. The findings indicated that food festivals, such as the Tjap Legende Festival and Surabaya Food Festival, have the potential to enhance the city’s image, introduce traditional cuisine, and promote local economic growth. Furthermore, these festivals serve as effective branding tools by leveraging local cultural elements and utilizing digitalization for promotion. Cross-sector collaboration, including SME empowerment and training, is crucial in creating a positive impact and ensuring sustainability. The study also emphasized the importance of financial and technological support for local artists, as well as the use of cultural narratives in promotion to attract tourists, particularly the younger generation and international visitors. Overall, food festivals in Surabaya have substantial potential to position the city as a competitive culinary destination at both national and global levels.Keywords: branding; tourist destination; food festival; traditional cuisine; SurabayaAbstrakSurabaya, sebagai kota yang memiliki potensi besar dalam sektor pariwisata kuliner tradisional, belum sepenuhnya dimanfaatkan secara optimal sebagai destinasi kuliner utama. Penelitian ini bertujuan untuk mengeksplorasi peran food festival dalam memperkuat citra Surabaya sebagai destinasi kuliner tradisional. Pendekatan penelitian yang digunakan adalah kualitatif, dengan melibatkan wawancara mendalam terhadap pelaku UMKM, pengunjung festival, dan penyelenggara acara, serta analisis observasi dan materi promosi. Hasil penelitian menunjukkan bahwa food festival, seperti Festival Tjap Legende dan Surabaya Food Festival, berpotensi meningkatkan citra kota, mengenalkan kuliner tradisional, serta mendorong pertumbuhan ekonomi lokal. Selain itu, festival ini juga berfungsi sebagai alat branding yang efektif dengan memanfaatkan elemen budaya lokal dan pemanfaatan digitalisasi dalam promosi. Kolaborasi lintas sektor, yang meliputi pemberdayaan UMKM dan pelatihan, memiliki peran penting dalam menciptakan dampak positif dan keberlanjutan. Penelitian ini juga menekankan pentingnya dukungan finansial dan teknologi untuk seniman lokal serta penerapan narasi budaya dalam promosi guna menarik wisatawan, khususnya generasi muda dan wisatawan internasional. Secara keseluruhan, food festival di Surabaya memiliki potensi yang besar untuk membangun citra kota sebagai destinasi kuliner yang kompetitif di tingkat nasional maupun internasional.Kata kunci: branding; destinasi wisata; food festival; kuliner tradisional; surabaya